Modeling a System of Rotating Biological Contactor (RBC) for Biodegradation of Phenol in Industrial Wastewater - Kekpugile, Dagde Kenneth; Kiasira, Piagbo Beabu (International Journal of Chemical and Process Engineering Research, 2015)
A model for a 4-stage Rotating Biological Contactor (RBC) for the biodegradation of phenol from industrial wastewater has been developed using the mass conservation principles. The kinetics for biodegradation of phenol and oxygen utilization were obtained from literature under the same operating conditions. The systems of non-linear differential ordinary differential equations obtained were integrated numerically using the fourth-order Runge-Kutta algorithm adapted to a Visual Basic 6.0 computer program. Model predictions of 0.0505mg/l obtained for effluent phenol concentration, compares favorably well with the plant data of 0.05mg/l with a maximum deviation of 1.0%. A biodegradation of approximately 70mg/l at residence time of approximately 10hours, 56mg/l at residence time of approximately 8.5hours, 57mg/l at residence time of approximately 7.5hours, and 68mg/l at residence time of approximately 6.0hours with a constant oxygen concentration utilization of 0.087mg/l, were obtained from the first, second, third and fourth-stage respectively. Functional parameters such as retention time, rotational speed, respiratory coefficient and biomass concentration were simulated to study its effect with a view to obtain optimum efficiency.